Hybrid Fluorescence and Frequency-Domain Photoacoustic Microscopy for Imaging Development of Parhyale hawaiensis Embryos - George J. Tserevelakis; Emmanouela Tekonaki; Maria Kalogeridi; Ioannis Liaskas; Anastasios Pavlopoulos; Giannis Zacharakis (Photonics, 2023)
Parhyale hawaiensis is a marine crustacean which has emerged as a powerful model organism to study molecular and cellular mechanisms linked to embryonic development and regenerative processes. Recently, several fluorescence-based optical microscopy techniques have been employed for the study of Parhyale to obtain anatomical descriptions, analyze gene expression patterns and reconstruct cell lineages. Aiming at the expansion of the imaging repertoire for this emerging model organism, we introduce a low-cost hybrid diagnostic system which integrates confocal fluorescence and frequency domain photoacoustic (FDPA) microscopy modalities, concurrently capturing both the radiative and radiationless relaxations of molecules following their excitation by an intensity-modulated laser source. We initially characterize the hybrid microscope in terms of PA signal generation efficiency and lateral spatial resolution, and subsequently evaluate its capabilities for the in vivo imaging of unlabelled and fluorescently labelled Parhyale embryos found at different stages of development. The recorded hybrid images have revealed a remarkable contrast complementarity between the integrated imaging modes, providing valuable information regarding cells’ structure, nuclei location, cellular membranes and yolk distribution. Our findings may pave the way for the broader adoption of inexpensive hybrid optical and PA microscopy methods in developmental biology, significantly upgrading the capabilities of the currently used technologies.